Pengaruh Beasiswa terhadap Motivasi Belajar Mahasiswa pendidikan Ekonomi 2022 di Universitas Negeri Medan - Meiriza, Mica Siar; Tarigan, Desry Rasmita; Naibaho, Novianti; Sinurat, Melvany; Siagian, Hernita (Ikatan Da'i Indonesia, 2024)
Education plays an important role in improving community welfare and sustainable development. However, the high cost of education is an obstacle for Indonesian people. To overcome this problem, the government provides assistance in the form of scholarships, in accordance with Law no. 20 of 2003 concerning the National Education System. Scholarships can be received from various institutions, and are educational financial assistance for students who excel but have low economic status. This research focuses on the effect of scholarships on student learning motivation, with normality test results showing a normal distribution of residual values. Simple linear regression analysis provides an equation model Y=16.91+0.89X, with R of 26.2%, indicating the contribution of the independent variable X to the dependent variable Y. The conclusion highlights the importance of scholarship support in increasing student learning motivation. Scholarships have a positive and significant impact, although their impact can be influenced by certain factors. Linear regression analysis also validated the significance of the model, showing that scholarships contribute to students’ learning motivation. In order support education policy, the results of this research are expected to provide insight for policy makers and related parties.